Family Harmony and Self Regulation Predict Student Learning Motivation: Keharmonisan Keluarga dan Pengaturan Diri Memprediksi Motivasi Belajar Siswa - Maulidia Bati Awwahah; Eko Hardi Ansyah (Academia Open, 2025)
General Background: Learning motivation is a central component in educational achievement and student development, shaped by internal and external determinants. Specific Background: Previous evidence indicates that family environment and self-regulation capacity are critical determinants associated with students’ engagement, goal orientation, and academic participation, particularly within Islamic secondary school contexts. Knowledge Gap: Earlier studies frequently investigated family harmony and self-regulation independently, with limited empirical examination of their combined relationship with learning motivation among MTs students. Aims: This study examines the relationship between family harmony and self-regulation with learning motivation among students at MTs Fadllillah. Results: Using a quantitative inferential design with 228 students selected through accidental sampling, data were collected using validated psychological scales and analyzed through multiple linear regression. Findings demonstrated a statistically significant relationship between family harmony and self-regulation with learning motivation, indicated by F(2,225) = 118.209 and p < 0.001. The coefficient of determination showed that both variables contributed 51.2% to learning motivation variance. Partial analysis also revealed significant relationships between family harmony and learning motivation, as well as between self-regulation and learning motivation. Novelty: This research integrates internal and external determinants of learning motivation simultaneously within an Islamic junior secondary education setting, providing a comprehensive analytical perspective. Implications: The findings provide empirical evidence supporting the importance of supportive family relationships and self-management capacity in strengthening student engagement, offering insights for educational practitioners and policymakers in designing student development strategies. Highlights: Combined Parental Relationship Quality and Personal Management Capacity Explain More Than Half of Academic Engagement Variance. Household Relational Stability Shows Statistically Significant Association With Student Academic Drive. Personal Behavioral Control Capacity Demonstrates Strong Statistical Association With Academic Engagement Patterns. Keywords: Family Harmony, Self Regulation, Learning Motivation, MTS Students, Multiple Linear Regression